Bilateral pheochromocytoma after kidney transplantation in neurofibromatosis type 1. (23rd May 2019) - de Miguel, Valeria; Paissan, Andrea; García Marchiñena, Patricio; Jurado, Alberto; Isola, Mariana; Alfie, José; Fainstein-Day, Patricia
Summary: We present the case of a 25-year-old male with a history of neurofibromatosis type 1 and bilateral pheochromocytoma 4 years after kidney transplantation that was successfully treated with simultaneous bilateral posterior retroperitoneoscopic adrenalectomy. Learning points: Hypertensive patients with NF1 should always be screened for pheochromocytoma. Pheochromocytoma is rarely associated with transplantation, but it must be ruled out in patients with genetic susceptibility. Posterior retroperitoneoscopic adrenalectomy (PRA) allows more direct access to the adrenal glands, especially in patients with previous abdominal surgeries.